2009
DOI: 10.1016/j.engfracmech.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Boundary effect on weight function in nonlocal damage model

Abstract: Some insights on boundary effects in nonlocal damage modelling are addressed. Interaction stresses that are at the origin of nonlocality are expected to vanish at the boundary of a solid, in the normal direction to this boundary. Existing models do not account for such an effect. We introduce tentative modifications of the classical nonlocal damage model aimed at accounting for this boundary layer effect in a continuum modelling setting. Computations show that some nonnegligible differences may be observed bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 20 publications
1
61
0
Order By: Relevance
“…The difference from the nonlocal stress at the points of the interior domain is that it is defined only for boundary layer thickness as a whole and not for an arbitrary generic point across the thickness. Further note that the local treatment of the stress in the boundary layer has previously been advocated for the deterministic nonlocal models, to introduce diminishing nonlocality as the boundary is approached (Krayani et al 2009). It has been shown that the proposed nonlocal boundary layer model agrees well with the original weakest-link model for structures with regular geometries, e.g., rectangular beams under pure bending (Bažant et al 2010).…”
Section: Review Of Weakest-link Model and Its Nonlocal Extensionmentioning
confidence: 99%
“…The difference from the nonlocal stress at the points of the interior domain is that it is defined only for boundary layer thickness as a whole and not for an arbitrary generic point across the thickness. Further note that the local treatment of the stress in the boundary layer has previously been advocated for the deterministic nonlocal models, to introduce diminishing nonlocality as the boundary is approached (Krayani et al 2009). It has been shown that the proposed nonlocal boundary layer model agrees well with the original weakest-link model for structures with regular geometries, e.g., rectangular beams under pure bending (Bažant et al 2010).…”
Section: Review Of Weakest-link Model and Its Nonlocal Extensionmentioning
confidence: 99%
“…In addition, it is straightforward to employ more sophisticated damage mechanisms such as anisotropic damage models. The treatment of nonlocal quantities in the vicinity of the boundary also requires some modifications according to the works of Krayani et al (2009), Pijaudier-Cabot andDufour (2010). A study is also necessary on the interactive radius, a parameter that is usually determined by experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Jirasek (1998) explored different non-local formulations based on the type of non-local variables. Boundary effects in non-local models must be avoided (Pijaudier-Cabot and Grégoire 2014) which is accomplished by normalizing the weight function or using only the local material response on the boundaries (see also, Krayani et al 2009;Pijaudier-Cabot and Dufour 2010). For the finite element framework, Pijaudier-Cabot and Huerta (1991) derived the general form of the tangent stiffness matrix for non-local isotropic damage models (see also, Askes and Sluys 2000).…”
Section: State-of-the-art Review Of Interface Elasticitymentioning
confidence: 99%
“…Several analytical, experimental and numerical studies demonstrated that the evolution of micro-cracks cannot occur arbitrarily fast due to inertia effects [26][27][28]. Thus, if damage is used to describe microcracking , its evolution has to be retarded in case of high strain rates, i.e.…”
Section: Rate-dependent Damage Modelmentioning
confidence: 99%